Gonadal dysgenesis in disorders of sex development: Diagnosis and surgical management. Issue 6 (December 2016) - Wolffenbuttel, K.P.; Hersmus, R.; Stoop, H.; Biermann, K.; Hoebeke, P.; Cools, M.; Looijenga, L.H.J.
Summary: Recent studies on gonadal histology have improved the understanding of germ cell malignancy risk in patients with disorders of sex development (DSD), and evidence-based gonadal management strategies are gradually emerging. Especially in 46, XY DSD and 45, X/46, XY DSD, which are characterized by gonadal dysgenesis, the risk of germ cell malignancy is significantly increased. This paper summarized the progress over the past 10 years in malignancy risk assessment in patients with DSD, and its implications for optimal surgical handling of the involved gonads.